Role of CO2 Laser on SBS between Dental Porcelain and Composite Resin Repair Process - Noor Bader Hassan; Basima Mohammed Ali Hussein; Ahmed Ali Mohammed (International Journal of Dentistry)
Background. The surface modification of porcelain material can be conducted by mechanical, chemical, or laser means. This study investigated the CO2 laser effect on porcelain to enhance bonding with composite resin. Materials and methods. A total of 33 blocks of feldspathic porcelain were randomly divided into 3 groups of 10. Additionally, three specimens were used in scanning electronic microscopy and energy-dispersive spectroscopy tests. Group I was treated with 9.5% hydrofluoric acid (HF), Group II with a 5 W CO2 laser, and Group III with CO2 followed by etching with 9.5% HF. Then, a Bisco intraoral repair kit was used, followed by the application of repair composite resin (Tetric N Ceram) on the porcelain surface using a Teflon mold and light-curing source. Shear bond strength (SBS) was assessed by using a digital universal testing machine, and failure modes were evaluated. Data were analyzed by analysis of variance (ANOVA) and least significant difference test. Results. A high significant difference in roughness and SBS was found amongst the tested groups P<0.001. SBS and roughness for Group III were significant at P<0.05, and the lowest value was observed in Group II. The cohesive mode of failure was dominant in Groups I and III, whereas adhesive failure was dominant in Group II. Conclusion. The surface treatment of porcelain with CO2 laser followed by HF application can enhance roughness and SBS, and can be recommended when extra retention during repair indication.